The role of Belgrade museums in tourism - Ljubica Vladušić; Bojan Ćirić (Mенаџмент у хотелијерству и туризму, 2016)
Using mutual efforts, tourism and culture as complementary branches can accomplish their goal - an increased number of tourists taking part in cultural tourism, which can be partly achieved by visiting museums. Of all the cities in Serbia, Belgrade has the largest number of museums. In this paper, museums are observed as a part of the cultural offer in Belgrade, with special reference to the National Museum as the oldest one, the Museum of the History of Yugoslavia as the most visited museum in Serbia, and the tourist manifestation of the Night of Museums. The importance of this paper is in defining the limiting factors that should be used in favour of increasing the influence of museums' on the Belgrade tourism offer, as well as highlighting a number of factors that can positively affect the achievement of this goal. To point out the positive and negative aspects of the performance in all three institutions, multi-criteria analysis of the museums in Belgrade was used. The key findings are integrated and the future direction of development is defined by using the process of synthesis. Furthermore, statistical and comparative methods are used in the analysis of the number of visits to Belgrade museums and comparisons of some of the museums are made in order to obtain the overall picture of the place the Belgrade museums have in tourism.